The long-chain flavodoxin FldX1 improves the biodegradation of 4-hydroxyphenylacetate and 3-hydroxyphenylacetate and counteracts the oxidative stress associated to aromatic catabolism in Paraburkholderia xenovorans - Laura Rodríguez-Castro; Roberto E. Durán; Valentina Méndez; Flavia Dorochesi; Daniela Zühlke; Katharina Riedel; Michael Seeger (Biological Research, 2024)
Abstract Background Bacterial aromatic degradation may cause oxidative stress. The long-chain flavodoxin FldX1 of Paraburkholderia xenovorans LB400 counteracts reactive oxygen species (ROS). The aim of this study was to evaluate the protective role of FldX1 in P. xenovorans LB400 during the degradation of 4-hydroxyphenylacetate (4-HPA) and 3-hydroxyphenylacetate (3-HPA). Methods The functionality of FldX1 was evaluated in P. xenovorans p2-fldX1 that overexpresses FldX1. The effects of FldX1 on P. xenovorans were studied measuring growth on hydroxyphenylacetates, degradation of 4-HPA and 3-HPA, and ROS formation. The effects of hydroxyphenylacetates (HPAs) on the proteome (LC–MS/MS) and gene expression (qRT-PCR) were quantified. Bioaugmentation with strain p2-fldX1 of 4-HPA-polluted soil was assessed, measuring aromatic degradation (HPLC), 4-HPA-degrading bacteria, and plasmid stability. Results The exposure of P. xenovorans to 4-HPA increased the formation of ROS compared to 3-HPA or glucose. P. xenovorans p2-fldX1 showed an increased growth on 4-HPA and 3-HPA compared to the control strain WT-p2. Strain p2-fldX1 degraded faster 4-HPA and 3-HPA than strain WT-p2. Both WT-p2 and p2-fldX1 cells grown on 4-HPA displayed more changes in the proteome than cells grown on 3-HPA in comparison to glucose-grown cells. Several enzymes involved in ROS detoxification, including AhpC2, AhpF, AhpD3, KatA, Bcp, CpoF1, Prx1 and Prx2, were upregulated by hydroxyphenylacetates. Downregulation of organic hydroperoxide resistance (Ohr) and DpsA proteins was observed. A downregulation of the genes encoding scavenging enzymes (katE and sodB), and gstA and trxB was observed in p2-fldX1 cells, suggesting that FldX1 prevents the antioxidant response. More than 20 membrane proteins, including porins and transporters, showed changes in expression during the growth of both strains on hydroxyphenylacetates. An increased 4-HPA degradation by recombinant strain p2-fldX1 in soil microcosms was observed. In soil, the strain overexpressing the flavodoxin FldX1 showed a lower plasmid loss, compared to WT-p2 strain, suggesting that FldX1 contributes to bacterial fitness. Overall, these results suggest that recombinant strain p2-fldX1 is an attractive bacterium for its application in bioremediation processes of aromatic compounds. Conclusions The long-chain flavodoxin FldX1 improved the capability of P. xenovorans to degrade 4-HPA in liquid culture and soil microcosms by protecting cells against the degradation-associated oxidative stress.